Doctor’s Responsibility in Providing Telemedicine Services among Health Care Facilities: Legal and Professional Dimensions - Radian Pandhika; Muhammad Fakih (Fakultas Hukum Universitas Lampung, 2021)
To provide specialist health care closer and improve quality in health care facilities, especially for remote areas, the central government utilizes information and communication technology through telemedicine services among health care facilities. This matter is regulated in the Ministry of Health Regulation No. 20 Tahun 2019 tentang Penyelenggaraan Telemedicine Antar Fasilitas Pelayanan Kesehatan. This article aims to describe the forms of legal responsibility and professional responsibilities of doctors in telemedicine services among health care facilities. The method used in this study is normative juridical. The study results show that physicians' responsibilities in telemedicine services among health care facilities can be divided into legal responsibilities (which are divided into civil, criminal, and administrative) and professional responsibilities (ethics and discipline). Doctors’ responsibility in telemedicine services among health care facilities is an obligation that doctors must fulfill because obligations are nothing but part of the tasks carried out in a particular work environment.